2022
DOI: 10.3390/ma15082831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest Maturity on the Chemical and Energetic Properties of Corn Stover Biomass Combustion

Abstract: Over the last decade, there has been increased interest in applying biomass as a raw material for producing biofuels used for thermochemical conversions. Extensive use of biomass could lead to controversial competition for arable land, water, and food; therefore, only waste materials and agricultural by-products and residues should be used to produce biofuels. One suitable by-product of agricultural production is crop residue from the harvest of maize for grain (corn stover). The harvest residues of corn stove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Their characteristics can be manually adjusted based on the differences in the proportions of each component, making them suitable for a wider range of product applications. Thirdly, the basic formula is composed of biopolymers, plasticisers, solvents, and other raw materials, and each component can be fully biodegradable [25]. Films developed on this basis have been proven to effectively biodegrade in natural environments [26].…”
Section: Confirmation Of the Formulamentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristics can be manually adjusted based on the differences in the proportions of each component, making them suitable for a wider range of product applications. Thirdly, the basic formula is composed of biopolymers, plasticisers, solvents, and other raw materials, and each component can be fully biodegradable [25]. Films developed on this basis have been proven to effectively biodegrade in natural environments [26].…”
Section: Confirmation Of the Formulamentioning
confidence: 99%
“…When the dry film could be separated, it was gently pulled down with tweezers to remove it from the bottom of the mould and then placed in an open space for about 24 to 48 h to ensure that the material was fully stable. The processing method mainly used heat condensation, and no difficult-to-dispose chemicals were added in order to minimise pollution to the environment as much as possible throughout the entire process [24][25][26][27][28][29]. After completion, a total of four control experimental groups were designed and implemented, all conducted in indoor conditions with a natural temperature of 12 °C and a relative humidity of 85%.…”
Section: Materials Processingmentioning
confidence: 99%
“…Carbon influences the calorific value through its high energy content, combustion heat, ratio to other elements, chemical structure of the biomass, and combustion efficiency [94]. Wojcieszek et al [95] reported that the heat of combustion of fresh maize cob kernels ranges from 7.62 to 10.79 MJ kg −1 , while that of seasoned kernels varies from 16.19 to 16.53 MJ kg −1 . High-quality maize biomass contains 47-54% carbon [96].…”
Section: The Biomass Of Zea Mays and Its Energy Valuementioning
confidence: 99%
“…This mainly concerns the total moisture content, which reduces the calorific value of the fuel [17]. According to Wojcieszak [18], the average calorific value of fresh maize cobs is 7.62-10.79 MJ kg −1 , while after drying, it increases to 16.19-16.53 MJ kg −1 . In an experiment conducted by Magdziarz and Wilk [19], the calorific value of plant biomass (woody biomass-pellets and agricultural biomass-oats) was about 18 MJ kg −1 , while that of hard coal was about 24 MJ kg −1 .…”
Section: Introductionmentioning
confidence: 99%